Pemberdayaan Masyarakat Desa melalui BUMDes Arih Ersada di Desa Raya - Tarigan, Dewi Natasia Br; Suharyanto, Agung; Deliana, Marlina (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
This article aims to find out how Community Empowerment in Raya Village is done through BUMDes Arih Ersada and find out what the obstacles are in the empowerment process using the Delivery Team theory (Totok Mardikanto) with the variables Location Selection Stage, Socialization Stage, Empowerment Process Stage and Community Self-Reliance Stage. The method used in this research is a descriptive qualitative research method using observation, interview and documentation data collection techniques. From the research results, it can be concluded that the location selection stage was quite good because before determining the location, deliberations were held with the community. The socialization stage carried out by BUMDes Arih Ersada was quite good, because most people already knew about the existence and benefits of BUMDes and participated in the socialization held. The empowerment process stage is not yet optimal because the business unit being run is still in the construction and development stage. The self-reliance stage is not yet optimal because it is still in process, but the village government has carried out outreach and training to the community. The inhibiting factor is capital, this happens because the business unit run by BUMDes is hit by a natural disaster so it requires a lot of money to build and develop the business unit. Lack of awareness and community participation, even though community participation will be able to offset the limited costs and capabilities of the village government and BUMDes managers in achieving the implementation of the Arih Ersada BUMDes program.